Data Collection Model and Data Accuracy of Fish Catches From the Bouke Ami Vessel in PPN Karangantu, Banten Province - Hamzah, Asep; Irnawati, Ririn; Syauqi, Muhamad (Agrikan Jurnal Agribisnis Perikanan, 2024)
The accuracy of catch production data is an important component in efforts to develop the capture fisheries sector and as a basis for policy making. The aim of this research is to find out how the data collection model occurs at PPN Karangantu and how high the level of accuracy of the data produced is. The method used in this research is a comparative method. Data was obtained through direct recording in the field by following the fishing trip of the Bouke Ami ship. The results of the research show that the level of accuracy of the data obtained at PPN Karangantu is classified as close to accurate because the results of the samples tested show an average level of data accuracy (TKD) of 95%. The data collection model in PPN Karangantu is a mixed data collection model, where PPN Karangantu records manually, then compares it with e-logbook data owned by fishermen and online weighing data.